Case Report: Herceptin as a Potentially Valuable Adjuvant Therapy for a Patient With Human Epidermal Growth Factor Receptor 2-Positive Advanced Esophageal Squamous Cell Carcinoma - Han, Li; Pan, Chi; Ni, Qingtao; Yu, Tao (Frontiers in Oncology, 2021)
Esophageal cancer is one of the most common cancers with a low overall 5-year relative survival rate of approximately 20%. Trastuzumab (Herceptin®) targets HER2 and is an effective therapeutic strategy in HER2-positive breast cancer. However, few reports have described targeted therapy for treating esophageal squamous cell carcinoma (ESCC). A patient with advanced ESCC who had received chemotherapy, radiotherapy, and had undergone a clinical study is described here. The tumor had not been controlled. Herceptin and chemotherapy were used as salvage therapy in this patient because of high HER2 expression. Good therapeutic results were observed in this patient. Therefore, Herceptin is a potential target therapy for patients with HER2-positive advanced ESCC. A study with a large population and a prospective random study are necessary to validate these results.